Aerobic oxidative synthesis of 3, 5-disubstituted isoxazoles directly from α, β-unsaturated ketones. (1st October 2016) - Li, Zheng; Wen, Gong; Fu, Rugang; Yang, Jingya
Using an efficient aerobic oxidative method, the synthesis of ten 3, 5-disubstituted isoxazoles by treatment of α, β-unsaturated ketones with hydroxylamine and NaOH at room temperature has been achieved.